Spermidine inhibits vascular calcification in chronic kidney disease through modulation of SIRT1 signaling pathway. Issue 6 (9th May 2021) - Liu, Xiaoyu; Chen, An; Liang, Qingchun; Yang, Xiulin; Dong, Qianqian; Fu, Mingwei; Wang, Siyi; Li, Yining; Ye, Yuanzhi; Lan, Zirong; Chen, Yanting; Ou, Jing‐Song; et al.
Abstract: Vascular calcification is a common pathologic condition in patients with chronic kidney disease (CKD) and aging individuals. It has been established that vascular calcification is a gene‐regulated biological process resembling osteogenesis involving osteogenic differentiation. However, there is no efficient treatment available for vascular calcification so far. The natural polyamine spermidine has been demonstrated to increase life span and protect against cardiovascular disease. It is unclear whether spermidine supplementation inhibits vascular calcification in CKD. Alizarin red staining and quantification of calcium content showed that spermidine treatment markedly reduced mineral deposition in both rat and human vascular smooth muscle cells (VSMCs) under osteogenic conditions. Additionally, western blot analysis revealed that spermidine treatment inhibited osteogenic differentiation of rat and human VSMCs. Moreover, spermidine treatment remarkably attenuated calcification of rat and human arterial rings ex vivo and aortic calcification in rats with CKD. Furthermore, treatment with spermidine induced the upregulation of Sirtuin 1 (SIRT1) in VSMCs and resulted in the downregulation of endoplasmic reticulum (ER) stress signaling components, such as activating transcription factor 4 (ATF4) and CCAAT/enhancer‐binding protein homologous protein (CHOP). Both pharmacological inhibition of SIRT1 by SIRT1 inhibitor EX527 and knockdown of SIRT1 by siRNA markedly blocked the inhibitory effect of spermidine on VSMC calcification. Consistently, EX527 abrogated the inhibitory effect of spermidine on aortic calcification in CKD rats. We for the first time demonstrate that spermidine alleviates vascular calcification in CKD by upregulating SIRT1 and inhibiting ER stress, and this may develop a promising therapeutic treatment to ameliorate vascular calcification in CKD. Abstract : We reported that spermidine (Spd) inhibits calcification of vascular smooth muscle cells, arterial rings and aortas in rats with chronic kidney disease (CKD). Furthermore, SIRT1 signal is critical for the inhibitory role of Spd in vascular calcification. Taken together, these findings provide the first evidence that Spd inhibits arterial calcification through modulation of SIRT1 and ER stress signals, suggesting that Spd may act as a novel SIRT1 modulator to treat arterial calcification.